2016
DOI: 10.1016/j.jelechem.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

l -Cysteine determination in embryo cell culture media using Co (II)-phthalocyanine modified disposable screen-printed electrodes

Abstract: Thiol-containing compounds such as L-cysteine have been demonstrated to play an important role in metabolism and cellular growth, acting as powerful antioxidants.Consequently, their analytical determination in biological media has received a considerable amount of attention. In this work, an electrochemical sensor for the accurate electroanalytical determination of L-cysteine is proposed, based upon a Co(II)-phthalocyanine nanoparticle bulk modified disposable screen-printed graphite electrode (CoPc-SPE). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…For example, Banks et al [ 3 , 4 ] have shown that metal oxide (bismuth, antimony, and tin) bulk modified screen-printed electrodes can offer a suitable platform for the sensing of heavy metals. Additionally, screen-printed platforms have been utilized, both as-is (unmodified) and modified, within many sensing applications, for example, towards the detection of biomolecules (such as lactate [ 5 ] or L-cysteine [ 6 ]), gases (such as O 2 [ 7 ] or CO [ 8 ]), and metals (such as Sb and Sn [ 9 ]); with particular success within the food industry, a key indication of their quality and versatility, with respect to capsaicin [ 10 ] and garlic [ 11 ] which have been successfully analysed with screen-printed electrodes (SPEs). An important parameter to consider when utilising electrochemical sensors is the real electroactive area, especially within fundamental calculations of electrochemical processes, as well as providing a methodology for their benchmarking with respect to the quality control of SPEs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Banks et al [ 3 , 4 ] have shown that metal oxide (bismuth, antimony, and tin) bulk modified screen-printed electrodes can offer a suitable platform for the sensing of heavy metals. Additionally, screen-printed platforms have been utilized, both as-is (unmodified) and modified, within many sensing applications, for example, towards the detection of biomolecules (such as lactate [ 5 ] or L-cysteine [ 6 ]), gases (such as O 2 [ 7 ] or CO [ 8 ]), and metals (such as Sb and Sn [ 9 ]); with particular success within the food industry, a key indication of their quality and versatility, with respect to capsaicin [ 10 ] and garlic [ 11 ] which have been successfully analysed with screen-printed electrodes (SPEs). An important parameter to consider when utilising electrochemical sensors is the real electroactive area, especially within fundamental calculations of electrochemical processes, as well as providing a methodology for their benchmarking with respect to the quality control of SPEs.…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine (RSH) can be electro‐oxidized to disulfide cysteine (RS‐SR) by Fe 3+ ions in the PB or PB‐Ammine structures, which is reduced to Fe 2+ . The generic reaction for cysteine oxidation on the surfaces of the modified SPEs has been proposed as follows: trueFe3++2RSHKobsFe2++4ptRS-SR+4pt2H+ …”
Section: Resultsmentioning
confidence: 99%
“…Over the recent decades, electroanalytical methods have received great attention from researchers, companies and clinical laboratories due to the simplicity of the procedures, speed of response, high reproducibility, satisfactory sensitivity and low costs . This set of characteristics allows the application of electrochemical methods in the determination of biomarkers , active pharmaceutical ingredient , food ingredients and pollutants . Because of this, the development of screen‐printed electrodes (SPEs) have become a revolution in the world of electrochemical sensors .…”
Section: Introductionmentioning
confidence: 99%
“…associated with a chemical reaction. 54 The use of electrochemistry for analytical purposes includes quality control, 55 environmental, 56,57 food 43,58 and biomedical 45,59 applications to name a few. These are typically dynamic processes that occur at the electrode-electrolyte interface.…”
Section: Electroanalytical Methods Towards the Detection Of Heavy Metals In Drinking Watermentioning
confidence: 99%